2021
DOI: 10.1016/j.pmedr.2021.101480
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine willingness: Findings from the COVID-19 effects on the mental and physical health of Asian Americans & Pacific Islanders survey study (COMPASS)

Abstract: Willingness to get the COVID-19 vaccine is crucial to reduce the current strain on healthcare systems and increase herd immunity, but only 71% of the U.S. public said they would get the vaccine. It remains unclear whether Asian Americans and Pacific Islanders (AAPI), a population with existing inequalities in COVID-19 infection and mortality, are willing to get the vaccine, and the factors associated with vaccine willingness. Given this imperative, we used data from a national, cross-sectional, comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 31 publications
3
29
1
Order By: Relevance
“…What is known about vaccine hesitancy among Native Hawaiian or Pacific Islanders is often contradictory because studies which combine them with Asian Americans report their hesitancy as lower than other racial/ethnic groups, 23 while those that separate them find their hesitancy to be higher. 24 Our results demonstrate that the proportion of Asian Americans who had vaccinated their children (12–17) and who said they would get their children (0–11) vaccinated right away was more than twice the proportion of Native Hawaiian or Pacific Islanders reporting the same. This further supports the need for disaggregation of data between Asian Americans and Native Hawaiian or Pacific Islanders, 16 as this gap between intentions to vaccinate children right away was among the widest of any racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 63%
“…What is known about vaccine hesitancy among Native Hawaiian or Pacific Islanders is often contradictory because studies which combine them with Asian Americans report their hesitancy as lower than other racial/ethnic groups, 23 while those that separate them find their hesitancy to be higher. 24 Our results demonstrate that the proportion of Asian Americans who had vaccinated their children (12–17) and who said they would get their children (0–11) vaccinated right away was more than twice the proportion of Native Hawaiian or Pacific Islanders reporting the same. This further supports the need for disaggregation of data between Asian Americans and Native Hawaiian or Pacific Islanders, 16 as this gap between intentions to vaccinate children right away was among the widest of any racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 63%
“…For example, research on NHPIs tends to aggregate them with Asian Americans (Chang et al, 2020 ). Studies combining these groups report they have low levels of vaccine hesitancy (Niño et al, 2021 ); however, studies which distinguish them reveal NHPIs have much higher COVID-19 vaccine hesitancy compared to Asian Americans (Ta Park et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent national survey demonstrated a link between racial discrimination and increased vaccine hesitancy in a sample of 2650 Americans [ 55 ]. Prior studies using COMPASS data showed that AAPIs’ willingness to receive and concerns related to the COVID-19 vaccine varied across cultural groups [ 56 , 57 ]. These findings suggest that discrimination may be a key factor in explaining the disproportionately lower COVID-19 vaccine uptake, particularly among individuals/groups who historically, and in light of COVID-19-related anti-Asian sentiments, have already experienced discrimination or anticipate facing discrimination, and consequently, thwarting pandemic response.…”
Section: Discussionmentioning
confidence: 99%